(untitled) (LEARNing Landscapes, 2012)
Newly certified, unemployed teachers in Ontario, Canada are volunteering in schools as a way to gain access to the teaching profession. This paper reports the case of one volunteer teacher in Ontario who reported informal learning and acquisition of professional knowledge as central to his volunteer experience. Specifically, the participant demonstrated learning in the areas of (1) pedagogy and classroom management and (2) non-instructional duties and responsibilities. Implications for unemployed teachers, teacher education, and administration are discussed.